Prostitusi Semarang Pasca 1852 - Iman Dwi Hartanto; R Reza Hudiyanto (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2023)
AbstractThe mention of women who choose a profession to work in the field of prostitution, every era has a different mention, there is a mention of jalir which was used in the previous royal era, there is also a mention of public women which was used during the Dutch East Indies period, followed by prostitutes and when this term becomes more refined as a prostitute. During the Dutch East Indies era, the prostitution sector received special attention from the government at that time because it had a direct impact on workers in the Dutch East Indies, from soldiers to government officials. At first the Colonial Government only gave burdens to the perpetrators without having binding laws related to prostitution so that the resulting impact was the spread of venereal diseases among the citizens of the Dutch East Indies. This was the end of the Dutch East Indies Government requiring special efforts to deal with the emerging social phenomena. The concrete effort that was made was the enactment of a rule in 1852 so that the government had control over the effects of rampant prostitution. The writing of this article uses historical methods to trace how the Colonial Government's efforts to deal with the problem of prostitution in the colonies.Keywords: prostitution, Dutch East Indies, modernizationAbstrakPenyebutan perempuan-perempuan yang memilih profesi untuk bekerja di bidang prostitusi, setiap zaman memiliki penyebutan yang berbeda-beda, ada penyebutan jalir yang dipakai pada zaman kerajaan terdahulu, ada juga penyebutan wanita publik yang digunakan selama masa Hindia Belanda, diikuti dengan pelacur serta pada saat ini penyebutannya menjadi lebih halus sebagai wanita tuna susila. Pada masa Hindia Belanda, sektor prostitusi ini mendapatkan perhatian khusus dari pemerintahan saat itu dikarenakan memiliki banyak sekali dampak secara langsung terhadap para pekerja di Hindia Belanda, mulai dari para tentara, hingga para pejabat pemerintahan. Pada mulanya Pemerinahan Kolonial hanya memberikan kebebaan pada para pelakunya tanpa memiliki hukum yang mengikat terkait prostitusi sehingga dampak yang dihasilkan adalah menyebarnya penyakit kelamin pada warga Hindia Belanda. Inilah akhirnya Pemerintahan Hindia Belanda memerlukan usaha khusus untuk menangani fenomena sosial yang muncul tersebut. Usaha konkit yang dilakukan adalah dengan diberlakukannya suatu aturan pada tahun 1852 agar pemerintah memiliki kendali terhadap damak prostitusi yang merajalela. Penulisan artikel ini mengguakan metode sejarah untuk melacak bagaimana usaha Pemerintah Kolonial menangani permasalahan prostitusi di tanah jajahan.Kata kunci: prostitusi, hindia belanda, modernisasi